2022
DOI: 10.1021/acs.orglett.2c01680
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective C6–H Hydroxyalkylation of Purines and Purine Nucleosides via α-C–H Functionalization of Alcohols at Room Temperature

Abstract: The highly regioselective C6–H hydroxylalkylation of purines and purine nucleosides within 10 min via the α-C­(sp3)–H functionalization of alcohols at room temperature is reported here for the first time. The reaction tolerated various functional groups, which have the potential for further modification to afford other valuable molecules. The reported method avoids metal catalysts, light, and protecting groups, giving a direct strategy to access 6-substitued alkylated purines and nucleosides with pharmaceutica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…We noticed that the Fukui index of the purine ring, as calculated by Yu, Yuan, and co-workers, showed that C 6 possessed a much higher f + value (Fukui function for nucleophilic attack) than C 8 and C 2 . This finding was remarkably consistent with the experimentally observed reactive site, as demonstrated by significant progress in the regioselective radical C 6 -functionalization of the purine ring . In order to clarify the reactivity difference between the two carbons (C 2 and C 8 ) as well as assess the viability of the intended regioselectivity, we initiated our investigation by calculating the condensed Fukui functions of protonated adenosine.…”
Section: Introductionsupporting
confidence: 82%
“…We noticed that the Fukui index of the purine ring, as calculated by Yu, Yuan, and co-workers, showed that C 6 possessed a much higher f + value (Fukui function for nucleophilic attack) than C 8 and C 2 . This finding was remarkably consistent with the experimentally observed reactive site, as demonstrated by significant progress in the regioselective radical C 6 -functionalization of the purine ring . In order to clarify the reactivity difference between the two carbons (C 2 and C 8 ) as well as assess the viability of the intended regioselectivity, we initiated our investigation by calculating the condensed Fukui functions of protonated adenosine.…”
Section: Introductionsupporting
confidence: 82%
“…As is generally known, purine consists of an electron-deficient pyrimidine and an electron-rich imidazole partner ( Scheme 1 d). In other previous work and our own work, when purines were exposed to nucleophilic reagents such as Grignard reagents [ 17 , 18 , 19 , 20 ] and nucleophilic radical agents (Minisci reaction) [ 21 , 22 , 23 , 24 , 25 , 26 ], the regioselectivity of the reaction predominantly lay at the electron-deficient 6-position [ 12 , 13 , 14 , 15 , 16 ]. In contrast, when the electrophilic bromine was introduced, a C 8 -brominated purine derivative was obtained ( Scheme 1 c).…”
Section: Introductionmentioning
confidence: 99%
“…12 The S–Se bond energy in selenosulfonates is low (172 kJ mol −1 ), and this can facilitate the generation of electrophilic sulfonyl radical species via homolytic cleavage of the S–Se bond under visible-light irradiation. Because of our particular interest in nitrogen heterocyclic chemistry, 13 in this study we designed a series of dienes and investigated their use in the synthesis of important eight-membered benzo[ b ]azocine derivatives via a novel photochemically driven, sulfonyl-centered, radical-initiated tandem cyclization that involves a chemoregioselective 8-endo cyclization-addition. Energetically favorable sulfonyl-radical cascade cyclizations to five- or six-membered N-heterocycles (Scheme 1a) 9,10 and azocines synthesis via ionic reactions have been reported.…”
Section: Introductionmentioning
confidence: 99%